Herbal Candy Feed Berbasis Teknologi Tepat Guna dari Limbah Cangkang Kerang untuk Penguatan Ekonomi Masyarakat Pesisir - Umi Kalsum; Brahmadhita Pratama Mahardhika; Restu Millaningtyas; Mohamad Bastomi; Moch Noerhadi Sudjoni; Anang Habibi (Universitas Nurul Jadid, 2026)
Semiring Village, Mangaran District, Situbondo Regency, faces two major challenges: the accumulation of shell waste that remains underutilized and the occurrence of mineral deficiency in cattle, which negatively affects animal health and productivity. These conditions highlight the need for an innovation that integrates coastal waste management with the provision of locally sourced feed supplements. This community service program aimed to implement herbal candy feed technology based on shell waste as a solution for waste management and mineral supplementation in cattle while promoting product diversification to strengthen the local economy. The innovation involved processing shell waste through cleaning, drying, crushing, and grinding into calcium-rich shell flour, which was then formulated with rice bran, molasses, mineral salt, premix, urea, and herbal extracts of turmeric and temulawak (Curcuma xanthorrhiza) to produce herbal candy feed. The novelty of this technology lies in the integration of coastal waste utilization, mineral supplementation, and appetite enhancement in a lick-block form that is more practical, durable, and easier to apply than conventional mineral supplementation. The program was conducted with farmer groups and the Millennial Sejahtera Group in Semiring Village, involving 40 participants through surveys, socialization sessions, focus group discussions, production training, and evaluation activities. The results showed an increase in participants’ knowledge of herbal candy feed from 60% to 100%, production skills from 10% to 100%, and understanding of ingredient-mixing techniques from 10% to 100%. The program also generated a diversified value-added product based on shell waste with the potential to improve livestock health, reduce environmental pollution, and create new business opportunities for coastal communities. Therefore, the implementation of herbal candy feed technology not only addresses technical challenges in cattle farming but also supports sustainable waste management and strengthens community economic resilience